Radiotherapy for cervical carcinoma in human immunodefi ciency virus-infected patients: A retrospective study - Tharavichitkul, Ekkasit; Meungwong, Pooriwat; Chakrabandhu, Somvilai; Klunklin, Pitchayaponne; Pukanhapan, Nantaka; Chitapanarux, Imjai (Biomedical Sciences and Clinical Medicine, 2024)
This was a retrospective study on the results of curative radiotherapy (with or without chemotherapy) for the treatment of cervical carcinoma patients who were infected with human immunodeficiency virus. This study was carried out in the Division of Therapeutic Radiology and Oncology, Department of Radiology, Faculty of Medicine, Chiang Mai University. Fifty-four patients were studied retrospectively from 2004 to 2009 and the CD4+ T cell count was assessed in 29 patients. According to FIGO staging, 25, 19, 9 patients and 1 patient were stage I, II, III and IV, respectively. The 2-year local control, disease-free survival and distant metastasis-free survival rates were 92.6%, 87% and 83.3%, respectively. During treatment, four (7.4%) and three (5.5%) patients developed grade 3-4 anemia and leucopenia, respectively. Serious late toxicity was observed in two patients with grade 3 hematuria.